2017
DOI: 10.2106/jbjs.16.01366
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Adult Acquired Flatfoot Deformity

Abstract: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(24 citation statements)
references
References 41 publications
0
22
0
2
Order By: Relevance
“…de Cesar Netto et al 2 prospectively evaluated multiple parameters used in measuring adult valgus flatfoot deformity, comparing CT images with and without load from 20 patients diagnosed with flexible deformity. These authors demonstrated that WBTC produced similar measurements to those traditionally obtained from conventional X-ray imaging to stage adult valgus flatfoot deformity.…”
Section: Case Reportsmentioning
confidence: 99%
See 3 more Smart Citations
“…de Cesar Netto et al 2 prospectively evaluated multiple parameters used in measuring adult valgus flatfoot deformity, comparing CT images with and without load from 20 patients diagnosed with flexible deformity. These authors demonstrated that WBTC produced similar measurements to those traditionally obtained from conventional X-ray imaging to stage adult valgus flatfoot deformity.…”
Section: Case Reportsmentioning
confidence: 99%
“…In this scenario, computed tomography (CT) allows acquisition of high-resolution images in different axes of the ankle and foot, and is usually used to evaluate fractures, degenerative changes, bone healing, and surgical planning for osteotomies, arthrodeses and arthroplasties. 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,20,36 WB CBCT produces images comparable with traditional CT in quality but does so with the foot in a loaded condition and with a markedly lower radiation dose. 6,30 Many authors have recently demonstrated the efficacy and reliability of WB CBCT in different foot alignment measures 9,10,20,29,30 ; however, to the best of our knowledge, there has not been an investigation on professional basketball.…”
mentioning
confidence: 99%